Spectrophotometric Determination of Ibuprofen and Nystatin Via Ion Pair Complex Formation Using Chromotrope 2R - Intisar Shihab; Theiaa Al-Sabha (College of Education for Pure Sciences, 1970)
This research paper tackles a developed method for Ibuprofen and Nystatin drugs determination both in their pure form and pharmaceutical formulations. The proposed method is based on the formation of binary complexes (ion association complexes) between the above drugs and Chromotrope 2R (C2R) in acidic medium forming a reddish orange colour. The complexes show maximum absorption at 562 nm and 566 nm for Ibuprofen and Nystatin respectively. The method was adhering to the Beer's law over concentration range 10-90 and 2-40 μg/ml with molar absorptivity values 1.36×103 and 7.59×103 l. mol-1. cm-1and average recovery 99.77% and 100.60 % for the above mentioned drugs respectively. No observed interferences appeared from the excipients commonly existed in pharmaceuticals. Successfully, application for both Ibuprofen and Nystatin was conducted in their pharmaceutical formulations.